THE ROLE OF PERCEIVED VALUE IN MEDIATING THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER SATISFACTION - M.G. Andika Yudistira Kawisana; Ni Wayan Ekawati (Riviera Publishing, 2024)
Tourism is one of the critical sectors that drives the Indonesian economy. This research is intended to determine the role of perceived Value in mediating the relationship between service quality and customer satisfaction (study at the Bedugul Recreation Warung in Tabanan district). The number of samples taken was 117 people using non-probability sampling methods, especially purposive sampling, namely samples determined using specific criteria. Data collection was carried out by distributing questionnaires at the Bedugul Recreation Stall. The data analysis techniques used are path analysis and the Sobel test. This analysis shows that service quality positively and significantly affects perceived Value. Service quality has a positive and significant effect on customer satisfaction. Perceived Value mediates the influence of service quality on customer satisfaction. This research implies that it can be used as material for consideration and input for management at Bedugul Recreation Warung in Tabanan Regency in marketing their products by considering service quality and perceived Value on customer satisfaction.